FORMATION OF MECHANISMS OF MANAGEMENT OF ORGANIZATIONAL DEVELOPMENT OF THE ORGANIZATION - I. Sitnikov (Вестник университета)
In conditions of realization of the new concept of economic development of Russia requires new approaches in economic policy. For the implementation of new approaches should take into account external factors of development of individual industries and complexes in the financial sector and public administration. The article suggests approaches that implement this concept, and presented in the form of a working algorithm.